The determinants of service imports: The role of cost pressure and financial constraints - Elena Biewen; Daniela Harsch; Julia Spies (Institut für Angewandte Wirtschaftsforschung (IAW), 2012)
This study provides evidence on how German multinational firms restructured their service activities during the last decade. Making use of new micro-level data on service imports of German multinationals from 2002-2008, we assess the determinants of service offshoring along the extensive and intensive margins. In particular, we evaluate how internal frictions in terms of lower sales level (per employee) and external frictions in terms of a reduced availability of credit co-determine the likelihood and the extent of sourcing services from abroad. First, we find a decreasing probability of starting to import services from abroad if firms are already under cost pressure. By contrast, firms intensify existing linkages of service imports in times of a sales drop. Second, financial constraints, which play a major role for goods trade, do not have any significant effect on service imports. These results are in line with the argument that the generally observed crisis-resilience of service trade stems from increased pressures to save on variable costs through offshoring and from its lower dependence on external finance. Furthermore, we find that a decline in sales and labor productivity induces firms to sort into intra-firm rather than arm's-length trading.
Keywords: F12; F15; L13; 330; Service Imports; Intra-Firm Trade; Arm's-Length Trade